Penerapan K-Means Clustering dalam Pengelompokan Kasus Tuberkulosis di Provinsi Jawa Barat - Fadhlan Sulistiyo Hidayat; Rizma Berliana Putri Affandi; Virgaria Zuliana; Tesa Nur Padilah (Peneliti.net, 2022)
Tuberculosis is a very common infectious disease and is lethal in most of the cases. This is the background of this research, namely because there are many cases of Tuberculosis in Jawa Barat. According to data obtained from the Open Data Jabar, namely Tuberculosis Data in Jawa Barat Province, showing data that in 2020 all districts and cities in Jawa Barat had a number of Tuberculosis cases starting from 320 cases in Banjar Regency which was the lowest case, and 10,248 cases in Bogor Regency which is the highest case in Jawa Barat. The purpose of this study was to cluster TB cases into high and low categories based on gender. The data we use is data on the number of TB cases in Jawa Barat province in 2020 which consists of 27 districts/cities. In this study using the Clustering method with the K-Means algorithm. The results obtained based on the test, the clusters obtained were 2 with cluster 0 with 23 low TB cases and 4 clusters for high TB cases. Researchers hope that the results of this study can become knowledge for the government to reduce the number of TB in Jawa Barat